Role of efflux pump(s) in intrinsic resistance of Pseudomonas aeruginosa: resistance to tetracycline, chloramphenicol, and norfloxacin. - Li, X Z (1994)
Most strains of Pseudomonas aeruginosa are significantly more resistant, even in the absence of R plasmids, to many antimicrobial agents, including beta-lactams, tetracycline, chloramphenicol, and fluoroquinolones, than most other gram-negative rods. This broad-range resistance has so far been assumed to be mainly due to the low permeability of the P. aeruginosa outer membrane. The intrinsic-resistance phenotype becomes further enhanced in "intrinsically carbenicillin-resistant" isolates, which were often assumed to produce outer membranes of even lower permeability. It has been shown, however, that this hypothesis cannot explain the beta-lactam resistance of these isolates (D.M. Livermore and K.W.M. Davy, Antimicrob. Agents Chemother. 35:916-921, 1991). In this study, we examined the uptake of tetracycline, chloramphenicol, and norfloxacin by intact cells using strains showing widely different levels of intrinsic resistance. Their accumulation and the response to the addition of a proton conductor showed that even relatively susceptible strains of P. aeruginosa actively pump out these compounds from the cell and that the efflux activity becomes much stronger in strains showing higher levels of intrinsic resistance. We conclude that the efflux mechanism(s) are likely to contribute significantly to the intrinsic resistance of P. aeruginosa isolates to tetracycline, chloramphenicol, and fluoroquinolones, as does the low permeability of the outer membrane. This conclusion is supported by the observation that the hypersusceptibility to various agents of the mutant K799/61 (W. Zimmermann, Antimicrob. Agents Chemother. 18:94-100, 1980) was apparently caused by the lack of active efflux. Although the hypersusceptibility of this mutant has hitherto been assumed to be solely due to its higher outer membrane permeability, its outer membrane was shown to have a coefficient of permeability to cephaloridine that was not significantly different from that of the parent, resistant strain K799/WT. The strains with elevated intrinsic resistance overproduced two cytoplasmic membrane proteins and one outer membrane protein; at least two of these proteins appeared different from the proteins overproduced in the recently described mutant with a derepressed multidrug efflux system, MexA-MexB-OprK (K. Poole, K. Krebes, C. McNally, and S. Neshat, J. Bacteriol. 175:7363-7372, 1993).